EFFECTIVENESS OF MATHEMATICS INTERVENTION PROGRAM (MIP) AMONG PRIMARY SCHOOL TEACHERS - Yazon, Alberto D; Leonano, Adora V (PEOPLE: International Journal of Social Sciences, 2019)
This one group pretest-posttest study examined the effectiveness of Mathematics Intervention Program (MIP) among 34 primary school teachers in Laguna, Philippines. Teacher’s competency in teaching Mathematics was measured in terms of content knowledge, teaching skills, material organization and presentation, management of learning environment, and teaching attitude. Meanwhile, teacher’s performance were gauged through pre-test, formative test, and post-test which contained the lessons on integers, decimals, fractions, power roots, algebraic expression and equation, measurement, and reasoning. The results showed that before the implementation of MIP, all teachers-participants were evaluated as less competent in teaching mathematics. Their performance based on pre-test results was also poor prior the MIP. During the conduct of this study, the primary school teachers obtained a satisfactory rating in their formative tests which advocated that the intervention program was helping them in improving their craft. The post-test result also marked an improvement in their competence and performance in teaching mathematics. Hence, the researchers concluded that the mathematics intervention program was effective in enhancing the pedagogical content knowledge among primary school teachers in mathematics. A more comprehensive study regarding teachers’ competencies and classroom performance may be conducted in the light of professional development and qualification standards for Mathematics teachers.